Ex-situ catalytic upgrading of vapors from microwave-assisted pyrolysis of low-density polyethylene with MgO. (1st October 2017) - Fan, Liangliang; Zhang, Yaning; Liu, Shiyu; Zhou, Nan; Chen, Paul; Liu, Yuhuan; Wang, Yunpu; Peng, Peng; Cheng, Yanling; Addy, Min; Lei, Hanwu; Ruan, Roger
Highlights: Vapors from microwave pyrolysis of LDPE were upgraded in a secondary catalyst bed. MgO was used as a base catalyst to upgrade the pyrolysis oil from LDPE. As high as 96.0% of gasoline-range hydrocarbons was obtained. Mechanisms for LDPE conversion with MgO were proposed. Abstract: Ex-situ catalytic upgrading of vapors from microwave-assisted pyrolysis of LDPE using MgO as the base catalyst was investigated and the effects of catalyst to reactant ratio, pyrolysis temperature, and catalytic reaction temperature on the yields and chemical profiles of products were examined. 24.2–38.5 wt.% of ex-situ upgraded liquid yield were obtained under varied reaction conditions. Productive gas yield (higher than 56.6 wt.%) and low solid residue yield (less than 7.1 wt.%) were obtained as long as the pyrolysis temperature was over 500 °C during the ex-situ upgrading process. The coke yield was negligible, ranging from 0.14 wt.% to 1.94 wt.% based on LDPE mass. The conversion of alkenes to aromatics was improved at higher catalyst to feedstock ratios, higher pyrolysis temperatures, and higher catalytic reaction temperatures. The total percentage of gasoline fraction in the upgraded pyrolysis oil ranged from 79.5% (37.3% mono-aromatics and 42.2% C5 -C12 aliphatics) to 96.0% (39.7% mono-aromatics and 56.3% C5 -C12 aliphatics) under various conditions, compared with 10.5% mono-aromatics and 30.2% C5 -C12 aliphatics from non-catalytic pyrolysis. The main composition of gas product was hydrogen, C1 -C3 olefins and paraffins, varying with reaction condition. Both free radical and carbanion mechanisms for the conversion of LDPE with MgO were proposed.